2020
DOI: 10.1111/jocn.15252
|View full text |Cite
|
Sign up to set email alerts
|

Feeling safe with patient‐controlled admissions: A grounded theory study of the mental health patients' experiences

Abstract: Aim To develop a grounded theory of the patients' experiences with patient‐controlled admission. Background Research indicates a potential for involving patients in mental health care, but there is a need to develop and investigate new approaches in health services. Patient‐controlled admission is an option for patients with severe mental disorders to refer themselves for a brief hospital admission when needed and thus avoid the usual admission procedure. Design Classic grounded theory with generation of a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
11
1
1
Order By: Relevance
“…This indicates that the shifting of gatekeeping powers to the patient and away from professionals and bureaucratic procedures is important. This fits well with the documented importance to be in control of aversive events, that clinical populations have lower level of control than non-patients [16], and that patients report safety as the core of the PCA benefit [17]. The favorable evaluation of PCAs in our study questions whether the possible gains from professionals symptom evaluations in the gatekeeping process should be considered more important than the possible gains from giving mental health patients more safety through controlling their own admissions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This indicates that the shifting of gatekeeping powers to the patient and away from professionals and bureaucratic procedures is important. This fits well with the documented importance to be in control of aversive events, that clinical populations have lower level of control than non-patients [16], and that patients report safety as the core of the PCA benefit [17]. The favorable evaluation of PCAs in our study questions whether the possible gains from professionals symptom evaluations in the gatekeeping process should be considered more important than the possible gains from giving mental health patients more safety through controlling their own admissions.…”
Section: Discussionsupporting
confidence: 78%
“…It is reasonable to think that more socializing stimulates improvement, but stable differences in patients' social style may also confound the observed relation. A recent qualitative study of patients with a PCA-contract found that they felt relating with staff were helpful, and if they felt ignored or pushed aside, they tended to withdraw from contact with staff [17]. This indicates that emphasizing and strengthening patient socializing might indeed improve outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In medical settings concern for the sense of safety experienced by patients (Ellegaard et al, 2020; Morton, 2020) and when exposed to disempowering aspects of care (Morton et al, 2020) is of interest in terms of quality of experience and speed of recovery. In one study, feeling safe during the process of hospitalization was found to increase feelings of control, calm and hope (Mollon, 2014).…”
mentioning
confidence: 99%
“…At the same time, the capacity and power generation efficiency of the aircraft power system have been continuously improved with the development of multielectric aircraft technology. The advantages of aviation variable frequency power supply without the need to continuously install converters have gradually emerged [ 1 ]. Three-phase converters, especially three-phase rectifiers, are crucial power conversion links in airborne electrical equipment.…”
Section: Introductionmentioning
confidence: 99%